Impact of Childhood Maltreatment on Recidivism in Youth Offenders: A Matched-Control Study - Li, Dongdong (Crim Justice Behav, 2015)
The purpose of the study is to examine the impact of childhood maltreatment on youth offender recidivism in Singapore. The study used case file coding on a sample of 3,744 youth offenders, among whom about 6% had a childhood maltreatment history. The results showed that the Youth Level of Service/Case Management Inventory 2.0 (YLS/CMI 2.0) ratings significantly predicted recidivism for nonmaltreated youth offenders, but not for maltreated youth offenders. Using propensity score matching, the result from a Cox regression analysis showed that maltreated youth offenders were 1.38 times as likely as their nonmaltreated counterparts to reoffend with a follow-up period of up to 7.4 years. The results implied that the YLS/CMI 2.0 measures were insufficient for assessing the risk for recidivism for the maltreated youth offenders, and that other information is needed to help assessors use the professional override when making the overall risk ratings.